Initiation of traditional birth attendants and their traditional and spiritual practices during pregnancy and childbirth in Ghana - Lydia Aziato; Cephas N. Omenyo (BMC Pregnancy and Childbirth, 2018)
Abstract Background Prior to the advent of modern obstetric services, traditional birth attendants (TBAs) have rendered services to pregnant women and women in labour for a long time. Although it is anticipated that women in contemporary societies will give birth in hospitals and clinics, some women still patronize the services of TBAs. The study therefore sought to gain an in-depth understanding of the initiation of TBAs and their traditional and spiritual practices employed during pregnancy and childbirth in Ghana. Methods The design was an exploratory qualitative one using in-depth individual interviews. Data saturation was reached with 16 participants who were all of Christian faith. Interviews were conducted with a semi-structured interview guide, audiotaped and transcribed verbatim. Content analysis was employed to generate findings. Results The findings showed that TBAs were initiated through apprenticeship from family members who were TBAs and other non-family TBAs as well as through dreams and revelations. They practice using both spiritual and physical methods and their work was founded on spiritual directions, use of spiritual artefacts, herbs and physical examination. TBAs delay cutting of the cord and disposal of the placenta was associated with beliefs which indicated that when not properly disposed, it will have negative consequences on the child during adulthood. Conclusion Although, TBAs like maternal health professionals operate to improve maternal health care, some of their spiritual practices and beliefs may pose threats to their clients. Nonetheless, with appropriate initiation and training, they can become useful.